FORMATION OF INTELLECTUAL AND EMOTIONAL CULTURE OF FUTURE CHEMISTRY TEACHERS IN COURSE CLASSES "ECOLOGICAL CHEMISTRY" (Pedagogy of Higher and Secondary Education, 2011)
In the article possibility of discussion, the use is shown as a method of future teachers' preparation to forming of intellectually-emotional culture for the children of school collective. An example of employment organization is made on-course "Ecological chemistry" for the students of chemical specialty of pedagogical and other directions of education.
Keywords: the intellectually-emotional cilture; ecological education; ecological chemistry